Analysis of comments and subtypes of comments in the daily nespapers Danas and Blic - Dojčinović Nikola; Jevtović Ana; Dojčinović Milan (Univerzitetska Misao)
Commentary and its subtypes are essential forms of journalistic expression. In them, the author analyzes, argues, evaluates, and interprets current events and phenomena, pointing out the causes, consequences, and further development of events to the audience. The objectives of this paper are to determine, by analyzing the content, the extent to which the dailies "Danas" and "Blic" meet the form of comments according to the literature, ie the rules of writing comments and its subtypes, as well as their representation in dailies. Based on the obtained results, it was determined that the commentary and its sub-column are more represented in the daily newspaper "Danas" than in the daily newspaper "Blic", while no editorial was identified in the analysis papers. The analysis of the content established that the required form of comments was partially respected in the comments of "Blic". What is missing in most of Blic's comments is argumentation, documentation, a clearly defined topic of comment, and detailed evaluation and interpretation. In the comments of "Danas", the authors use facts, to interpret, analyze, and socially evaluate events and phenomena. Also, the authors of the comments in "Danas" present more arguments and documentation, and in almost all comments there is an engaged position of the author. The topics are treated unequivocally, and the point of the comments is clearly visible. In some comments of "Danas" and "Blic", a hybrid form was noticed between the classic commentary and the column. Namely, some comments (which are highlighted in the sheets under "comment") lack documentation, arguments, and a conclusion with a forecast. In the above comments, the authors comment on phenomena or events from a very personal point of view, without arguing for or against, interpreting and analyzing.